Airborne volatile organic compounds in urban and industrial locations in four developing countries. (October 2015) - Do, Duc Hoai; Walgraeve, Christophe; Amare, Abebech Nuguse; Barai, Krishna Rani; Parao, Amelia Estigoy; Demeestere, Kristof; van Langenhove, Herman
Abstract: Volatile organic compounds (VOCs) represent an important class of air pollutants, however their concentration levels in developing countries have scarcely been reported in literature. Therefore, concentration levels of 60 VOCs were determined at 27 urban and industrial locations in seven different cities in Ethiopia, Vietnam, the Philippines and Bangladesh between 2011 and 2014. Active sampling using Tenax TA as a sorbent was employed followed by TD-GC-MS analysis using internal standard calibration. It was found that TVOCs concentration levels in Dhaka, Bangladesh (arithmetic mean: 343 and 399 μg/m 3 for urban and industrial campaign, respectively) were more than 10 times higher when compared to TVOCs levels observed in Mekelle, Ethiopia. ∑BTEX concentration at street sites ranges from 36 μg/m 3 in Mekelle, to 100 and 250 μg/m 3 in Hanoi, Vietnam and Dhaka, Bangladesh, respectively. The indoor to outdoor concentration ratios were found to be dependent on the country, type of environment, VOC compound and outdoor reference location. The highest Ozone Formation Potential (OFP, 2150 μg/m 3 ), calculated from the same set of seven aromatic VOCs, was obtained at the street site in Dhaka. This OFP value is a factor three and four times higher than the OFP value observed at the street sites in Hanoi, and Manila, respectively. Finally, the Cumulative Cancer Risk (CCR) calculated for four carcinogenic VOCs ranged from 97 × 10 −6 in urban Mekelle to 299 × 10 −6 in urban Dhaka. This work provides for the first time comparisons of CCR in urban and industrial environments in the selected developing countries. Highlights: Concentration of 60 VOCs are determined in four developing countries. Highest mean TVOC concentration (344 μg/m 3 ) is found in Dhaka, Bangladesh. Highest I/O ratio for TVOCs (21.8) is calculated for urban Manila, Philippines. Biggest contributor to the calculated OFP is toluene (35 ± 11%). CCR.10 6 values range from 97 in Mekelle, Ethiopia to 300 in Dhaka, Bangladesh.